2022
DOI: 10.3390/antiox11020404
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Microbial Volatile Elicitors Using a Transparent Methodology for Induction of Systemic Resistance and Regulation of Antioxidant Genes at Expression Levels in Chili against Bacterial Wilt Disease

Abstract: Microbial volatiles benefit the agricultural ecological system by promoting plant growth and systemic resistance against diseases without harming the environment. To explore the plant growth-promoting efficiency of VOCs produced by Pseudomonas fluorescens PDS1 and Bacillus subtilis KA9 in terms of chili plant growth and its biocontrol efficiency against Ralstonia solanacearum, experiments were conducted both in vitro and in vivo. A closure assembly was designed using a half-inverted plastic bottle to demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 112 publications
0
21
0
Order By: Relevance
“…The Pseudomonas species is the first microbe to be commercially used in various agricultural and industrial applications [30]. Pseudomonas possess many traits suitable for biocontrol and growth-promoting agents [31]. The main goal was to isolate and characterize Pseudomonas spp from tomato rhizosphere with the potential to promote plant growth in Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…The Pseudomonas species is the first microbe to be commercially used in various agricultural and industrial applications [30]. Pseudomonas possess many traits suitable for biocontrol and growth-promoting agents [31]. The main goal was to isolate and characterize Pseudomonas spp from tomato rhizosphere with the potential to promote plant growth in Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, within 30 min, the GR concentration in the tissues was seen to drop significantly and completely eliminated in 3 h. The half-life (t 1/2 ) of GR was between 20–30 min, suggesting that the GR was quickly cleared from the circulatory systems ( Li et al, 2019b ). M. oleifera was discovered to have a low bioavailability of iron because of the presence of high phytic acid ( Azlan et al, 2022 ; Kashyap et al, 2022 ). In contrast, M. oleifera leaves have high bioavailability of folate compounds.…”
Section: Pharmacokinetics Of M Oleiferamentioning
confidence: 99%
“…In contrast, M. oleifera leaves have high bioavailability of folate compounds. In a study of rat models, the folates from M. oleifera were proven to be 81.9% more bioavailable than the synthetic folates ( Saini et al, 2016 ; Kashyap et al, 2022 ). Despite that, the bioavailability of M. oleifera in various models may vary due to different chemical structures, solubility and their interactions with other compounds.…”
Section: Pharmacokinetics Of M Oleiferamentioning
confidence: 99%
“…19 Similarly, B. subtilis KA9 enhanced the overexpression of CAT-2, POD and superoxide dismutase (SOD), as well as numerous pathogenesis-related genes, inducing disease resistance in chili peppers to B. cinerea. 20 Xu et al reported that the treatment of postharvest apples and tomatoes with B. velezensis QSE-21 supernatant induced disease resistance against B. cinerea. 21 Although these advances demonstrate that Bacillus-induced disease resistance involves an antioxidant response that is probably produced by secreted antioxidant metabolites, the key compounds involved in this mechanism remain completely unexplored.…”
Section: Introductionmentioning
confidence: 99%